Communication of the blessed Eucharist to divorced persons? Analysis popes Francis adoration “Amoris laetitia” - JANCZEWSKI, ZBIGNIEW (Prawo Kanoniczne, 2017)
Many catholic peoples after divorce can receive the blessed Eucharist. New popes document “Amoris laetitia” details relative to that question. This elaboration in the first part shows Eucharist as expression of unity in the Church and marriage. Next part is about receiving Body of Christ by persons leaves in not sexual relations in the civil marriage. The last part is about Holly communion divorced persons on the scope of “Amoris laetitia”. This document not changes Doctrina of the Church in those matter. Pope Francis try changes only discipline of Roman Catholic Church.